Review of Islamic Law on Online-Based Loan Financing Practices in Society - Leni Leni; Udin Wahrudin; Fenny Damayanti Rusmana (International Journal of Economics, Management and Accounting (IJEMA), 2023)
The background of this research is the problem of online lending practices in fintech lending cash loans that have not been registered with the Financial Services Authority and how Islamic law reviews online lending practices in fintech lending cash loans that have not been registered with the Financial Services Authority. The purpose of this research is to determine the review of Islamic law regarding the practice of online-based loan financing in society. The method used in this research is qualitative. The results of this research indicate that the review of Islamic law regarding online lending practices in fintech lending cash loans that have not been registered with the Financial Services Authority is not in accordance with Islamic law, because it contains usury. First, usury is an addition to the principal debt which includes usury qardh. Second, usury is a fine if you are late in repayment or past the due date, which includes jahiliyah usury. Furthermore, the practice of online lending in fintech lending cash loans is not in accordance with Islamic law because it contains elements of gharar due to uncertainty and lack of clarity in the operational system or agreements that have been made.